EFFICIENT FINE-GRAINED DATA SHARING MECHANISM FOR ELECTRONIC MEDICAL RECORD SYSTEM. - E., DINESH; V., KARTHICK; S., NAVEENKUMAR; N., YOGESWARAN (Turkish Journal of Physiotherapy Rehabilitation, 2021)
Safe personal data storage is a key problem when using cloud providers because it contributes to a range of protection and data secrecy concerns. Data privacy protection, open data exchange, effective authority delegation, and computing efficiency optimization are all roadblocks to achieving realistic fine-grained access control in the Personal Information Sharing environment. It is essential to encrypt confidential data before uploading it to the cloud. To address the issues raised above, we recommend a Personal Data Exchange data sharing mechanism that provides data security, fine-grained access control, and authority delegation. The proposed methodology uses the duplicate generation technique with a two-server based computing facility to secure patients' MHR (Medical Health Record) in the healthcare cloud. The duplicate server serves as a second gallery, containing duplicate MHR that are mistaken for the original by the attacker. When a user uploads a file to the original server, a copy is created and stored on a different server. When an attacker attempts to access the system, the duplicate (decoy) files are named in this method; however, in our proposed methodology, the duplicate files are obtained from the beginning to ensure better protection. Encrypting medical records employs the AES algorithm.